PENGARUH MODEL PEMBELAJARAN TEAM GAMES TOURNAMENT (TGT) TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VIII MTs THAMRIN YAHYA RAMBAH HILIR PADA MATERI OPERASI ALJABAR - -, Roji’ah; Deswita, Hera; -, Arcat (Universitas Pasir Pengaraian, 2015)
The learning outcomes of mathematic problem at MTs Thamrin yahya had a problem. There were 50% who got score under KKM. This research gives solution by appiying Teams Games Tournaments (TGT) model. Hypothesis testing used t test. before conducting t test, homogeneity and normality test was conducted firstly. Normality test used liliefors test and homogeneity test used test wich was the result or normal distribution sample has homogeny varians. Then, hypothesis test was conducted which was the calculation of result was tcount = 5,26 and ttable = 2,008. It show that tcount > ttable at the 5% significan level effect of TGT learning model toward mathematics studi result.